The Effect of High-Intensity Interval Training (HIIT) Protocols on Enhancing Aerobic and Anaerobic Capacity: An Experimental Study on a Sample of Athletes - Rasheed Ghanim, Saif (Journal of Education, Health and Sport, 2026)
Purpose: The aim of this study was to determine the effect that a six-week high-intensity interval training program would have on anaerobic capacity, maximal sprint speed, and explosive power together with aerobic capacity among adult handball players. Methods: Eighteen male handball players (age: 24.26 ± 5.18 years) were randomly assigned into two groups of nine each, an experimental group and a control group. The experimental group intervened with a structured HIIT program three times per week for six weeks while the control group continued regular handball training. Performance variables included mean explosive power (vertical jump), mean anaerobic power (30-s step test), maximal sprint speed (60-m sprint), and maximal oxygen consumption (VO₂max; Cooper 12-min test). Pre- and post-intervention data were analyzed using paired and independent t-tests, with effect sizes calculated using Cohen’s d. Results: The HIIT group demonstrated significant improvements in all performance variables following the intervention (p < 0.001), including increases in explosive power (520.3 ± 58.7 to 589.6 ± 60.9 W; +13.3%, d = 1.17), anaerobic power (418.4 ± 47.5 to 465.2 ± 49.1 W; +11.2%, d = 0.98), maximal sprint speed (24.7 ± 1.4 to 26.2 ± 1.5 km·h⁻¹; +6.1%, d = 0.90), and VO₂max (46.1 ± 3.6 to 50.3 ± 3.8 ml·kg⁻¹·min⁻¹; +9.1%, d = 1.04). No significant changes were observed in the control group (p > 0.05). Post-test comparisons revealed significantly superior performance in the HIIT group across all variables (p ≤ 0.004). Conclusion: A six-week HIIT program effectively enhances anaerobic performance, sprint speed, explosive power, and aerobic capacity in handball players, representing a time-efficient conditioning strategy for meeting the sport’s high-intensity and intermittent performance demands.